Ninaâ€™s Characterization Reflected in the Speech Acts in Black Swan Film - Arina Lubsi; Dwijani Ratnadewi; Armeria Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
This thesis entitled Ninaâ€™s Characterization Reflected in the Speech Acts in Black Swan Film. Question of the research are what kinds of speech acts which show Ninaâ€™s double characters in the film â€œBlack Swanâ€, what are the intended meanings of those speech acts and why does Nina use those speech acts in film â€œBlack Swanâ€. This study is aimed to find the kinds of speech acts which show Ninaâ€™s double characters in the film â€œBlack Swanâ€, to analyze the intended meanings of those speech acts, and the last to explain why Nina uses those speech acts in film â€œBlack Swanâ€. This study makes reference to Yule, Searle and Taleb theory. This research is qualitative research. The data of the research are the utterances of Nina which have been obtained from the film script. From the data analysis, it is found that 15 utterances which have intended meaning spread by 5 macro classes of speech act : 6 utterances of representative, 5 utterances of Expressive, 2 utterances of directive, 1 utterance of commissive, and 1 utterance of declarative. Beside that, the reason of the use of speech act is because she is getting OCD (Obsessive Compulsive Disorder) which can create delusion in herself and destroy her life